The Effect of IFMIS Symbolic Adoption on Post-Acceptance Use Behavior: Moderated Analysis - Wiratmoko, Ambrosius Oki Tri; Roekhudin; Mardiati, Endang (SAFE-Network, 2024)
Integrated Financial Management Information System (IFMIS) is a a significant milestone in a country's budget reform agenda. The government of Indonesia has launched an IFMIS for work unit level called Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) in 2022. This research seeks to test the effect of TAM determinants on symbolic adoption and subsequent post-acceptance usage behaviour with individual absorptive capacity as moderator. This research is quantitative research, using PLS-SEM disjoint two-stage approach to assess symbolic adoption, a higher order construct consisting of four dimensions. 93 samples from ministry of public works and housing are analysed and found that both TAM determinants have a positive impact on symbolic adoption and symbolic adoption positively affect post-acceptance use behaviour. Individual absorptive capacity enhances the impact of symbolic adoption on explorative use, but does not moderate the effect on extended use. This research contributes to the field of symbolic adoption by demonstrating how individual absorptive capacity can shape the relationship between symbolic adoption and post-acceptance usage behaviour.